Knowledge, Attitudes and Practices of Menstrual Hygiene Management among Adolescent Girls in Community Schools - Nepal, Narayani (BMC Research Journal, 2026)
Menstrual hygiene is crucial for the health and dignity of adolescent girls, yet limited research has explored this topic in Nepal. This study aimed to assess the factors influencing knowledge, attitudes, and practices of menstrual hygiene among adolescent girls in grades 11 and 12 from five community schools of Siddartha Municipality. Five community schools were selected through purposive sampling, and students were selected using simple random sampling. Data were collected through self-administered questionnaires and interview schedule. The study revealed a mean age of participant was 17.1 years, with 91.1% reporting menarche between ages 10–14. While 82% perceived menstruation as a natural cycle, only 50.9% respondent identified the uterus as the source of menstrual blood. Mothers were the primary source of information for 69.9% of respondents. Better menstrual hygiene knowledge and practices were significantly associated with nuclear family setups and mothers with formal education.Findings indicated positive attitudes toward using sanitary pads (92.2%) and daily hygiene practices (92.3%). During menstruation, 91.1% used sanitary pads, 66.4% bathed daily, and 88.1% attended school. However, 63.7% reported physical challenges, while 16.7% experiences mental and 16.1% experienced social problem.The study suggests the need for continuous education on menstrual hygiene and government support to address gaps in facilities like clean water, toilets, and sanitary pads. And need of promoting comprehensive health education can help correct misconceptions and foster healthier practices among adolescent girls.